FAKTOR-FAKTOR YANG MEMPENGARUHI NON PERFORMING FINANCING (NPF) PADA BANK UMUM SYARIAH DI INDONESIA TAHUN 2010-2013 - Sri Wahyuni Asnaini (Journal Of Communication Education, 2017)
ABSTRACT This study aims to determine the factors that affect the Non Performing Financing (NPF) on Islamic Banks in Indonesia. The independent variable used in this study is the Gross Domestic Product (GDP), inflation, Financing Deposit Ratio (FDR), Bank Indonesia Certificates Sharia (SBIS), and Capital Adequacy Ratio (CAR). While Non Performing Financing (NPF) is the dependent variable. These results indicate that the variable of Bank Indonesia Certificates Sharia (SBIS) affect positively and significantly to the Non-Performing Financing (NPF). and variable Capital Adequacy Ratio (CAR) and significant negative effect on the Non-Performing Financing (NPF). While the variable Gross Domestic Product (GDP), inflation, and Financing Deposit Ratio (FDR) did not significantly affect the Non Performing Financing (NPF). Key words: Gross Domestic Product (GDP), inflation, Financing Deposit Ratio (FDR), Bank Indonesia Certificates Sharia (SBIS), Capital Adequacy Ratio (CAR), and Non-Performing Financing (NPF).